PENGARUH PERLAKUAN PENDAHULUAN PADA INKUBASI BIJI KAKAO KERING NON FERMENTASI DALAM BUFFER ASETAT TERHADAP SIFAT SENSORIS PASTA COKELAT GELAP - , Mukhammad iqbal Prawira Atmaja ([Yogyakarta] : Universitas Gadjah Mada, 2013)
when incubated in acetic buffer and its influence on The purpose of this study was to determine the role of pre-treatment of un- fermented dried cocoa beans the sensory properties of dark chocolate. Incubation was carried out in two stages, the first stage in acetic buffer medium pH 2.7, 600 mM for 24 hours, then a sec- ond stage in acetic buffer medium pH 5.5, 600 mM for 12 hours. While cocoa liq- uor roasting at of 120Â°C for 9 minutes. The The results showed that unfermented dried cocoa beans with fragment treatment obtained pH values and colour index higher than water immersion at 45oC for 16 hours treatment. The total polyphenols in the treatment of 45Â°C waterimmersion for 16 hours were higher than the total polyphenols contained in the fragment treatments. results of sensory evaluation of dark chocolate with cocoa liquor roasting showed that incubation of unfermented dried cocoa beans with pre-treatment given significant effect to decrease the intensity of bitterness and astringent. Fragment treatment has lower intensity in bitternes and astringent than treatment with immersion water at 45oC for 16 hours. Overall acceptance of the dark chocolate indicated that the panelists liked the unfermented dried cocoa beans with fragment treatment after dark chocolate was made from Ghana cocoa beans.